Model project dan implementasinya untuk meningkatkan aktivitas dan keterampilan berpikir kritis siswa Sekolah Dasar - Ihsan, Muhammad Aidi Noor; Agusta, Akhmad Riandy; Suzana, Yenny; Ningsih, Sri (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
The problem in this study is that the learning process does not yet emphasize training indicators of critical thinking skills and meeting the Civics learning objectives set out in the curriculum. An effort to overcome this problem is by implementing an innovative learning model called PROJECT in Civics learning. This learning model is a combination of the Problem-Based Learning, Jigsaw, and Make-A-Match learning models. This study aims to analyze the increase in activity and critical thinking skills after using the PROJECT learning model. This research applies Classroom Action Research (PTK) which is carried out in three meetings with stages consisting of planning, implementation, observation, and reflection. The object of this research was 8 students in fourth class SDN Simpang Empat 4, Banjar Regency. The results of this research showed that students who obtained the criteria were very active at meeting 1 with a percentage of 37, 5%, this result continued to increase until the final meeting reached a percentage of 87.5%. Students who obtained the criteria for highly skilled critical thinking at meeting 1 with a percentage of 37.5%, this result continued to increase with each meeting until at the last meeting it reached a percentage of 87.5%. Based on the research results, it can be concluded that the use of the PROJECT model can increase students' activities and critical thinking skills and student learning outcomes.